Tourism Development, Foreign Direct Investment, and Environmental Sustainability: How Green Technology Innovations Make a Difference - Xuan Zhou; Chang Hwan Choi (SAGE Open)
Tourism drives economic growth and impacts the environment. This study examines the nonlinear relationships among tourism development, economic growth, foreign direct investment, economic globalization, renewable energy consumption, and greenhouse gas (GHG) emissions in the Organization for Economic Co-operation and Development economies from 1995 to 2020. It also explores how green technological innovation (GTI) moderates and influences the link between tourism development and GHG emissions. We employ panel data analysis techniques, including fully modified ordinary least squares (FMOLS), dynamic ordinary least squares (DOLS), canonical cointegrating regression (CCR), feasible generalized least squares (FGLS), and the method of moments quantile regression (MMQR). We find an inverted U-shaped relationship between tourist numbers and GHG emissions and a U-shaped relationship between tourism receipts and GHG emissions. The moderating effect of GTI flattens the inverted U-shaped curve, thereby reducing the negative environmental impact of tourism to some extent. Our findings suggest that advancing GTI in the tourism industry is crucial for mitigating environmental degradation while promoting economic growth.